2017
DOI: 10.5213/inj.1732728.364
|View full text |Cite
|
Sign up to set email alerts
|

Potential Biomarkers for Diagnosis of Overactive Bladder Patients: Urinary Nerve Growth Factor, Prostaglandin E2, and Adenosine Triphosphate

Abstract: Mobile WebpISSN 2093-4777 eISSN 2093-6931 INTERNATIONAL NEUROUROLOGY JOURNALPurpose: This study aimed to investigate potential biomarkers for the diagnosis of overactive bladder (OAB). Methods: A total of 219 subjects were enrolled and divided into 2 groups: OAB subjects (n = 189) and controls without OAB symptoms (n = 30). Three-day voiding diaries and questionnaires were collected, and urinary levels of nerve growth factor (NGF), prostaglandin E2, and adenosine triphosphate were measured and normalized to ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In addition to its role as a physical barrier, the urothelium provides bi-directional communication with underlying primary afferents (Lazzeri, 2006; Birder and Andersson, 2013; Merrill et al, 2016) via the detection and/or release of a range of excitatory and inhibitory neurotransmitters and neuromodulators including ATP, acetylcholine, nitric oxide (NO), NGF, prostaglandin E2 (PGE2), neurokinin A, and inflammatory mediators as described above (and extensively reviewed by Birder et al) (Everaerts et al, 2010a,b; Birder and Andersson, 2013; de Groat and Yoshimura, 2015; Grundy et al, 2018a). Altered urothelial mediator release has been identified from OAB and IC/PBS patients in a number of studies and may be a compounding mechanism in the development of chronic neuronal hypersensitivity (Kim et al, 2005, 2006; Sun and Chai, 2006; Suh et al, 2017).…”
Section: Urothelial Permeabilitymentioning
confidence: 99%
“…In addition to its role as a physical barrier, the urothelium provides bi-directional communication with underlying primary afferents (Lazzeri, 2006; Birder and Andersson, 2013; Merrill et al, 2016) via the detection and/or release of a range of excitatory and inhibitory neurotransmitters and neuromodulators including ATP, acetylcholine, nitric oxide (NO), NGF, prostaglandin E2 (PGE2), neurokinin A, and inflammatory mediators as described above (and extensively reviewed by Birder et al) (Everaerts et al, 2010a,b; Birder and Andersson, 2013; de Groat and Yoshimura, 2015; Grundy et al, 2018a). Altered urothelial mediator release has been identified from OAB and IC/PBS patients in a number of studies and may be a compounding mechanism in the development of chronic neuronal hypersensitivity (Kim et al, 2005, 2006; Sun and Chai, 2006; Suh et al, 2017).…”
Section: Urothelial Permeabilitymentioning
confidence: 99%
“…Therefore, ROC analysis suggested that ROCK2, especially in combination with GEF or ADRB3, could act as an auxiliary biomarker for the diagnosis of OAB. Nerve growth factor [ 18 ] and brain-derived neurotrophic factor [ 19 ] have also both been proposed as potentially useful biomarkers for OAB patients. However, the potential of a relationship between urinary neurotrophins and the diagnosis of OAB has not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…In OAB syndrome, various urine biomarkers were extensively studied to distinguish phenotypes along with the diagnosis [3,4,38,39]. A representative example is nerve growth factor (NGF) and brain-derived neurotrophic factor, a neurotrophin that is produced in the urothelium or smooth muscle cells is widely used as a marker of lower urinary tract dysfunction.…”
Section: Urinary Biomarkers and Microbiome In Overactive Bladdermentioning
confidence: 99%